Tube-drawable glass, its method of manufacture and use - Patents.com
Through the glass formula of specific cation ratio and heat treatment process, the lack of optical and chemical stability of the LIDAR system shell materials is solved, and the optical performance of high transparency and low transparency is achieved. It is suitable for large-size pipe manufacturing, improving the finished product quality of the LIDAR system.
Patent Information
- Application Number
- JP2020210103
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-25
- Filing Date
- 2020-12-18
- Publication Date
- 2025-02-12
- Estimated Expiration
- 2040-12-18
AI Technical Summary
When manufacturing the shell of the LIDAR system, it is difficult for existing glass materials to have the characteristics of high transparency in the near-infrared range and low transparency in the visible light range. At the same time, there are problems of insufficient mechanical strength and chemical stability. Especially in the A-Draw method, crystallization is prone to occur, affecting molding and finished product quality.
A glass formula composed of cations such as silicon, boron, aluminum, sodium, potassium, chromium, cobalt is adopted to control the cation ratio and heat treatment process to achieve the characteristics of high transparency in the near infrared range and low transparency in the visible light range, and control the crystallization rate within the temperature range of 700°C to 1250°C to improve chemical stability and mechanical strength.
It achieves optical performance with high transparency in the near infrared range and low transparency in the visible range, and has excellent chemical stability and mechanical strength. It is suitable for large-size pipe manufacturing, avoiding crystallization, and is suitable for the shell of LIDAR system.
Smart Images

Figure 0007628818000005 
Figure 0007628818000001 
Figure 0007628818000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a tube-drawable glass, in particular a tube-drawable glass having good hydrolytic resistance and good chemical toughening, a method for producing said glass and the use of said glass. The glass according to the invention can be used in particular in the field of LIDAR (English "Light Detection And Ranging"), in particular as a LIDAR housing or a LIDAR cover. [Background technology]
[0002] LIDAR systems usually have a laser with radiation in the near infrared range (NIR range), in particular at wavelengths above 780 nm. The electromagnetic radiation emitted by the laser is at least partially reflected by objects in the vicinity of the LIDAR system and the reflected light is recorded by a corresponding sensor of the system. Based on the recorded light patterns, the LIDAR system can recognize the objects. Based on the so-called time of flight method (in English "Time of Flight (ToF)"), the distance can also be determined. Some LIDAR systems can measure the speed of an object based on the phase difference between the emitted and reflected light.
[0003] LIDAR systems are becoming increasingly important because they can be used in particular in the field of autonomous driving, which has become increasingly popular in recent years. LIDAR systems can also be used in many further fields, such as robotics, drones, satellites, marine technology, mining, construction, the railway sector, and many other fields.
[0004] To protect the sensitive optical components from environmental influences, LIDAR systems require a housing that separates them from the environment. However, to ensure the functionality of the system, this housing must allow the light emitted by the LIDAR laser to exit and the light reflected by the object back into the detector. Furthermore, the housing should be designed in such a way that no visible light can reach the interior from the exterior, or only to a very small extent. The same applies to the visible light in the reverse path from the interior to the exterior. The reason behind this is that the components inside should not be visible from the outside, because this can often be perceived as annoying. Furthermore, the interior should also be protected from annoying light from the exterior, which could damage the components or negatively affect the measurement results.
[0005] Traditionally, such housings have often been manufactured from polymer materials, in particular polycarbonate (PC) or polymethyl methacrylate (PMMA). However, such materials have drawbacks, especially with regard to scratch resistance, mechanical resistance, and chemical resistance. Glass can protect the sensor technology better than polymer materials, for example against water penetration (permeability) and other environmental influences (e.g. in the case of cars, road salt, exhaust fumes, and stress in car washes).
[0006] In particular, so-called black glass, which has a high transmittance in the NIR range and a low transmittance in the visible range, is suitable. For example, glasses having a high transmittance in the NIR range and a low transmittance in the visible range are described in WO 2019 / 065643 (WO2019 / 065643A1) or JP 07-126036 A.
[0007] However, the known glasses have the disadvantage that they cannot be produced by the so-called A-draw process. The A-draw process is a known method for producing tubular glasses. In contrast to the Danner or Vello process, the A-draw process allows the production of glass tubes with a diameter of 10 cm or more. Such glass tubes are particularly advantageous for producing LIDAR housings, since LIDAR systems usually have housings in the form of annular hollow cylinders. To be producible by the A-draw process, the glasses must have certain properties, in particular a sufficient resistance to crystallization for the drawing of the tubes. In particular, the drawability of the glasses, due to low devitrification and low dependence of the transmittance on the forming parameters, is of particular importance. The black glasses known so far do not have such properties. In particular, heated glasses, i.e. glasses which only become colored by a thermal aftertreatment (heat treatment process), are not suitable, since the transmittance is highly dependent on the forming parameters due to the absence of oxide-based color systems.
[0008] High crystallization resistance is particularly important for production in tube drawing. Otherwise, devitrification crystals may form, especially on the glass surface, which may, for example, prevent the shaping of the glass. Furthermore, during subsequent use in LIDAR systems, devitrification crystals may cause scattering effects, which may result in image errors and false images of the surroundings. Therefore, the glass should have good devitrification stability. This is particularly important for large dimensions and thick walls.
[0009] A further disadvantage of the glasses known so far is that, compared to polymeric materials, the chemical resistance is only moderately improved. In this respect, further improvements are desirable, especially for applications in the exterior area. Furthermore, in order to improve the stability against environmental influences (e.g. hail), the glasses should preferably be chemically toughenable. Furthermore, the glasses should have good melting properties. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] International Publication No. 2019 / 065643 [Patent Document 2] Japanese Patent Application Publication No. 07-126036 Summary of the Invention [Problem to be solved by the invention]
[0011] It is therefore an object of the present invention to overcome the drawbacks of the prior art. Said object is achieved by the subject matter of the claims. [Means for solving the problem]
[0012] In one embodiment, the present invention provides a maximum crystallization rate (KG) of up to 0.20 μm / min in the temperature range 700° C. to 1250° C., especially when the glass is heat treated in a gradient furnace with a temperature ramp for a holding time of 1 hour. max ) and hydrolysis resistance in accordance with hydrolysis class 1 according to ISO 720, wherein the ratio of the minimum transmittance in the wavelength range 850 nm to 950 nm to the maximum transmittance in the wavelength range 250 nm to 700 nm is in the range of 1.9:1 to 15:1 for a sample thickness of 2 mm.
[0013] In a further aspect, the present invention provides a cation of the following moiety: Ingredients Proportion Silicon 40~80 Boron 0~20 Aluminum 0~25 Sodium 2~22 Potassium 0.1-10 Chromium 0.05~0.5 Cobalt 0.03~0.5 in the indicated proportions (cation %), wherein the sum of the sodium and potassium cations is in the range of 10-25 cation %, the sum of the chromium and cobalt cations is in the range of 0.15-0.55 cation %, and the sum of the magnesium, calcium, strontium, barium and zinc cations is at most 15 cation %.
[0014] In particular, the present invention provides a maximum crystallization rate (KG) of up to 0.20 μm / min in the temperature range 700° C. to 1250° C. when the glass is heat treated in a gradient furnace with a temperature ramp for a holding time of 1 hour. max ) and a hydrolysis resistance in accordance with hydrolysis class 1 according to ISO 720, wherein the ratio of the minimum transmittance in the wavelength range 850 nm to 950 nm to the maximum transmittance in the wavelength range 250 nm to 700 nm is in the range of 1.9:1 to 15:1 for a sample thickness of 2 mm, and the glass has a cation content of the following components: Ingredients Proportion Silicon 40~80 Boron 0~20 Aluminum 0~25 Sodium 2~22 Potassium 0.1-10 Chromium 0.05~0.5 Cobalt 0.03~0.5 in the indicated proportions (cation %), wherein the sum of the sodium and potassium cations is in the range of 10-25 cation %, the sum of the chromium and cobalt cations is in the range of 0.15-0.55 cation %, and the sum of the magnesium, calcium, strontium, barium and zinc cations is at most 15 cation %.
[0015] The invention is based in part on the advantageous matching of the molar ratios of the cations to one another. It is therefore reasonable to express the glass composition in cation %. The glass of course also contains anions. However, the focus of the invention is on the cation composition.
[0016] The term cation percentage (abbreviated as "cation % (Kat.-%)") refers to the relative molar percentage of the relevant cation compared to the total percentage of all cations in the glass. The relative molar percentage of that anion compared to the total percentage of all anions in the glass is referred to herein as anion percentage (abbreviated as "anion %").
[0017] In addition to the cations, the glass contains anions. The anions are preferably O 2- , F - , Br - , Cl - and SO4 2- The anion is selected from the group consisting of O 2- The molar proportion of is preferably at least 50 anion %, more preferably at least 70 anion %, more preferably at least 90 anion %, more preferably at least 98 anion %, more preferably at least 99 anion %. In a preferred embodiment, the glass is fully oxidic, i.e. has as anion O 2- It contains only 1, 2 and no other anions.
[0018] The glass of the invention may contain anions of halogens, in particular the anions F, Cl and / or Br. Preferably, the total proportion of F, Cl and Br anions is at most 20 anion%, more preferably at most 10 anion%, more preferably at most 5 anion%, more preferably at most 3 anion%, more preferably at most 1 anion%. In a preferred embodiment, the glass is free of F, Cl and / or Br anions or contains F, Cl and Br anions in proportions of at most 3 anion%, at most 2 anion%, or at most 1 anion%, respectively. In one embodiment, the glass is free of Cl. -for example at least 0.1 anion %, at least 0.2 anion %, at least 0.5 anion %, at least 1 anion %, at least 2 anion %, or at least 3 anion %, in particular 0.5 to 10 anion %, or 1 to 5 anion %.
[0019] When a glass is described as containing a cation of a particular component in a percentage indicated as a cation %, this relates to the molar percentage of the sum of all cationic species of the named component, unless otherwise stated. For example, component M may be present in the glass in different oxidation numbers, e.g., M 2+ As, and M 3+ If the glass can exist as a cation of M in a proportion of x cation %, then a statement that the glass contains cations of M is 2+ and M. 3+ This means that the total percentage of x cations corresponds to x cation %.
[0020] The glasses of the present invention preferably contain silicon cations (especially Si 4+ ) in a proportion of 40 to 80 cationic %, more preferably 45 to 75 cationic %, even more preferably 50 to 70 cationic %. The proportion of silicon cations may be, for example, 40 to 70 cationic %, 45 to 70 cationic %, or 60 to 70 cationic %. This proportion of silicon cations is particularly advantageous with regard to the chemical resistance and hot formability of the glass. In contrast, a very high content of silicon cations leads to an increase in the energy demand for melting the glass. The proportion of silicon cations may be, for example, at least 40 cationic %, at least 45 cationic %, at least 50 cationic %, or at least 60 cationic %. The proportion of silicon cations may be, for example, up to 80 cationic %, up to 75 cationic %, or up to 70 cationic %.
[0021] The glass of the present invention contains boron cations (especially B 3+) in particular in a proportion of 0 to 20 cationic %, for example 1 to 19 cationic %, 2 to 18 cationic %, or 5 to 15 cationic %. In some embodiments of the invention, the proportion of boron cations is less than 5 cationic %, less than 2 cationic %, less than 1 cationic %, less than 0.5 cationic %, or less than 0.1 cationic %. The glass of the invention may be free of boron cations. The proportion of boron cations may be, for example, 1 to 15 cationic %, or 5 to 10 cationic %. The boron cations act as network modifiers and may in some circumstances hinder the solubility of the chromium cations. Therefore, the proportion of boron cations is preferably limited to an upper limit. The proportion of boron cations may be, for example, at least 1 cationic %, at least 2 cationic %, or at least 5 cationic %. The proportion of boron cations may be, for example, up to 20 cationic %, up to 19 cationic %, up to 18 cationic %, up to 15 cationic %, or up to 10 cationic %.
[0022] The glass of the present invention contains no aluminum cations (especially Al 3+), in particular in a proportion of 0 to 25 cationic %, for example 1 to 22.5 cationic %, 2 to 20 cationic %, 3 to 15 cationic %, or 5 to 12 cationic %. In some embodiments, the proportion of aluminum cations is less than 5 cationic %, less than 2 cationic %, less than 1 cationic %, less than 0.5 cationic %, or less than 0.1 cationic %. The glass of the invention may be free of aluminum cations. The proportion of aluminum cations may be, for example, 0 to 2 cationic %, 0.1 to 1.5 cationic %, or 0.5 to 1 cationic %. Aluminum cations act as network modifiers and can increase the devitrification stability of the glass. However, aluminum-containing raw materials often bring water into the melt, which can generate water vapor bubbles that are difficult to remove by fining. Therefore, the proportion of aluminum cations is preferably within the ranges listed above. The proportion of aluminum cations may be, for example, at least 0.1 cationic %, at least 0.5 cationic %, at least 1 cationic %, at least 2 cationic %, at least 3 cationic %, or at least 5 cationic %. The proportion of cations of aluminum may be, for example, up to 25 cations, up to 22.5 cations, up to 20 cations, up to 15 cations, up to 12 cations, up to 2 cations, up to 1.5 cations, or up to 1 cation.
[0023] The glasses of the present invention preferably contain sodium cations (especially Na +) in a proportion of 2 to 22 cationic %, more preferably 3 to 20 cationic %, more preferably 4 to 18 cationic %, more preferably 5 to 17 cationic %, for example 6 to 16 cationic %, or 8 to 14 cationic %. The proportion of sodium cations may be, for example, 12 to 20 cationic %, or 14 to 18 cationic %. Sodium cations can increase the solubility of sparingly soluble components, for example chromium cations and cobalt cations. Furthermore, sodium cations are advantageous with regard to the glass's ability for chemical hardening by ion exchange. On the other hand, sodium cations may impair chemical resistance. The proportion of sodium cations may be, for example, at least 2 cationic %, at least 3 cationic %, at least 4 cationic %, at least 6 cationic %, at least 8 cationic %, at least 12 cationic %, or at least 14 cationic %. The proportion of sodium cations may be, for example, up to 22 cationic %, up to 20 cationic %, up to 18 cationic %, up to 17 cationic %, up to 16 cationic %, or up to 14 cationic %.
[0024] The glass of the present invention preferably contains potassium cations (especially K + ) in a proportion of 0.1 to 10 cationic %, more preferably 0.5 to 9 cationic %, more preferably 1 to 8 cationic %, for example 1.5 to 7.5 cationic %, or 2 to 5 cationic %. The proportion of potassium cations may be, for example, 5 to 10 cationic %, or 6 to 9.5 cationic %. On the one hand, potassium cations can increase the chemical resistance. On the other hand, the contribution to increasing the solubility of chromium cations and cobalt cations is not so great. Furthermore, a high proportion of potassium cations has a negative effect on exchangeability. The proportion of potassium cations may be, for example, at least 0.1 cationic %, at least 0.5 cationic %, at least 1 cationic %, at least 1.5 cationic %, at least 2 cationic %, at least 5 cationic %, or at least 6 cationic %. The proportion of potassium cations may be, for example, up to 10 cationic %, up to 9.5 cationic %, up to 9 cationic %, up to 7.5 cationic %, or up to 5 cationic %.
[0025] Preferably, the glass according to the invention contains both sodium and potassium cations. The total proportion of sodium and potassium cations is preferably in the range of 10-25 cation %, more preferably 11-22.5 cation %, more preferably 12-20 cation %, for example 15-20 cation %. This has a positive effect on the melting and fining behavior. Furthermore, it increases the solubility of the cobalt and chromium cations. The total proportion of sodium and potassium cations may be, for example, at least 10 cation %, at least 11 cation %, at least 12 cation %, or at least 15 cation %. The total proportion of sodium and potassium cations may be, for example, up to 25 cation %, up to 22.5 cation %, or up to 20 cation %.
[0026] In view of the above-mentioned partially different properties and effects of sodium cations and potassium cations, the ratio of the molar percentage of sodium cations (cation %) to the molar percentage of potassium cations (cation %) is preferably in the range of 0.5:1 to 25:1, for example 1:1 to 20:1, 1.5:1 to 15:1, or 2:1 to 10:1. The ratio of the molar percentage of sodium cations (cation %) to the molar percentage of potassium cations (cation %) may be, for example, at least 0.5:1, at least 1:1, at least 1.5:1, or at least 2:1. The ratio of the molar percentage of sodium cations (cation %) to the molar percentage of potassium cations (cation %) may be, for example, up to 25:1, up to 20:1, up to 15:1, or up to 10:1.
[0027] Preferably, the glass according to the invention contains no or only a small proportion of other alkali metal cations besides sodium and potassium cations. In particular, the proportion of lithium cations is preferably less than 1 cation %, more preferably less than 0.5 cation %, preferably less than 0.1 cation %. Particularly preferably, the glass is free of other alkali metal cations than sodium and potassium, in particular free of lithium cations. It has been found that lithium cations can increase the devitrification rate.
[0028] As mentioned above, the glasses according to the invention are particularly advantageous for applications where low transmission in the visible range and high transmission in the NIR range are required, for example in the case of housings or covers in the LIDAR field.
[0029] One of the components that can be used according to the invention to achieve this spectral property is the chromium cation. The glass of the invention preferably comprises 0.05-0.5 cationic % of chromium, more preferably 0.1-0.4 cationic %, even more preferably 0.15-0.3 cationic %. The cationic % of chromium can be, for example, 0.05-0.4 cationic %, 0.1-0.3 cationic %, or 0.15-0.25 cationic %. The cationic % of chromium can be, for example, at least 0.05 cationic %, at least 0.1 cationic %, or at least 0.15 cationic %. The cationic % of chromium can be, for example, up to 0.5 cationic %, up to 0.4 cationic %, up to 0.3 cationic %, or up to 0.25 cationic %.
[0030] A further component preferably used to adjust the spectral properties is the cobalt cation. The glass of the invention preferably comprises cobalt cations in a proportion of 0.03-0.5 cationic %, more preferably 0.04-0.3 cationic %, more preferably 0.05-0.2 cationic %, more preferably 0.06-0.15 cationic %. The proportion of cobalt cations may be, for example, 0.04-0.4 cationic %, 0.05-0.3 cationic %, 0.06-0.2 cationic %, or 0.07-0.16 cationic %. The proportion of cobalt cations may be, for example, at least 0.03 cationic %, at least 0.04 cationic %, at least 0.05 cationic %, at least 0.06 cationic %, or at least 0.07 cationic %. The proportion of cobalt cations may be, for example, up to 0.5 cationic %, up to 0.4 cationic %, up to 0.3 cationic %, up to 0.2 cationic %, up to 0.16 cationic %, or up to 0.15 cationic %.
[0031] Preferably, the glass of the present invention contains both chromium and cobalt cations. The total proportion of chromium and cobalt cations is preferably in the range of 0.15-0.55 cation%, more preferably 0.17-0.50 cation%, more preferably 0.19-0.45 cation%, more preferably 0.21-0.40 cation%, more preferably 0.23-0.35 cation%, more preferably 0.25-0.30 cation%. The total proportion of chromium and cobalt cations may be, for example, at least 0.15 cation%, at least 0.17 cation%, at least 0.19 cation%, at least 0.21 cation%, at least 0.23 cation%, or at least 0.25 cation%. The total percentage of chromium cations and cobalt cations may be, for example, up to 0.55 cationic %, up to 0.50 cationic %, up to 0.45 cationic %, up to 0.40 cationic %, up to 0.35 cationic %, or up to 0.30 cationic %.
[0032] It has been found to be particularly advantageous for the spectral properties of the glass if the chromium cations are present in molar excess relative to the cobalt cations. Preferably, the ratio of the molar percentage of chromium cations (cation %) to the molar percentage of cobalt cations (cation %) is in the range of >1:1 to 5:1, more preferably 1.25:1 to 4:1, more preferably 1.5:1 to 3:1, more preferably 2.0:1 to 2.5:1. The ratio of the molar percentage of chromium cations (cation %) to the molar percentage of cobalt cations (cation %) may for example be >1:1, at least 1.25:1, at least 1.5:1, or at least 2.0:1. The ratio of the molar percentage of chromium cations (cation %) to the molar percentage of cobalt cations (cation %) may for example be at most 5:1, at most 4:1, at most 3:1, or at most 2.5:1.
[0033] It has been found that the solubility of cobalt cations and chromium cations can be significantly increased when sodium cations and potassium cations are present in significant molar excess. Preferably, the ratio of the total molar percentage (cation%) of sodium cations and potassium cations to the total molar percentage (cation%) of cobalt cations and chromium cations is in the range of 25:1 to 150:1, more preferably 30:1 to 125:1, more preferably 35:1 to 100:1, more preferably 40:1 to 90:1, more preferably 45:1 to 80:1, for example 50:1 to 75:1, or 55:1 to 70:1. The ratio of the total molar percentage (cation%) of sodium cations and potassium cations to the total molar percentage (cation%) of cobalt cations and chromium cations may be, for example, at least 25:1, at least 30:1, at least 35:1, at least 40:1, at least 45:1, at least 50:1, or at least 55:1. The ratio of the combined molar percentage of sodium and potassium cations (cation %) to the combined molar percentage of cobalt and chromium cations (cation %) can be, for example, at most 150:1, at most 125:1, at most 100:1, at most 90:1, at most 80:1, at most 75:1, or at most 70:1.
[0034] The glasses of the present invention may also contain further components.
[0035] The glass of the present invention contains magnesium cations (especially Mg 2+), preferably in a proportion of 0 to 5 cationic %, for example 0.1 to 2 cationic %, or 0.2 to 1 cationic %. The proportion of magnesium cations may be, for example, 0 to 2.5 cationic %, or 0.5 to 1.5 cationic %. The glass of the invention may be free of magnesium cations. The proportion of magnesium cations may be, for example, at least 0.1 cationic %, at least 0.2 cationic %, or at least 0.5 cationic %. The proportion of magnesium cations may be, for example, up to 5 cationic %, up to 2.5 cationic %, up to 2 cationic %, up to 1.5 cationic %, or up to 1 cationic %.
[0036] The glass of the present invention contains calcium cations (especially Ca 2+ ) preferably in a proportion of 0 to 15 cation%, for example 0.1 to 12 cation%, 0.2 to 10 cation%, or 0.5 to 7.5 cation%. The proportion of calcium cations may be 2 to 9 cation%, or 4 to 8 cation%. In other embodiments, the proportion of calcium cations may be, for example, 0 to 5 cation%, 0 to 1 cation%, or 0.25 to 1.5 cation%. In embodiments of the invention, the proportion of calcium cations is less than 0.5 cation%, or less than 0.1 cation%. The glass of the invention may be free of calcium cations. The proportion of calcium cations may be, for example, at least 0.1 cation%, at least 0.2 cation%, at least 0.25 cation%, at least 0.5 cation%, or at least 2 cation%. The cation percentage of calcium can be, for example, up to 15 cation%, up to 12 cation%, up to 10 cation%, up to 9 cation%, up to 8 cation%, up to 7.5 cation%, up to 5 cation%, up to 1.5 cation%, or up to 1 cation%.
[0037] The glass of the present invention contains strontium cations (especially Sr 2+) preferably in a proportion of 0 to 5 cationic %, for example 0.1 to 2 cationic %, or 0.2 to 1 cationic %. The proportion of strontium cations may be, for example, 0 to 2.5 cationic %, or 0.5 to 1.5 cationic %. Preferably, the proportion of strontium cations is at most 5 cationic %, more preferably at most 2.5 cationic %, more preferably at most 2 cationic %, more preferably at most 1.5 cationic %, more preferably at most 1 cationic %. Particularly preferably, the glass according to the invention is free of strontium cations. The proportion of strontium cations may be, for example, at least 0.1 cationic %, at least 0.2 cationic %, or at least 0.5 cationic %.
[0038] The glass of the present invention is preferably a barium cation (especially Ba 2+ ) preferably in a proportion of 0 to 5 cationic %, for example 0.1 to 2 cationic %, or 0.2 to 1 cationic %. The proportion of barium cations may be, for example, 0 to 2.5 cationic %, or 0.5 to 1.5 cationic %. Preferably, the proportion of barium cations is at most 5 cationic %, more preferably at most 2.5 cationic %, more preferably at most 2 cationic %, more preferably at most 1.5 cationic %, more preferably at most 1 cationic %. Particularly preferably, the glass according to the invention is free of barium cations. The proportion of barium cations may be, for example, at least 0.1 cationic %, at least 0.2 cationic %, or at least 0.5 cationic %.
[0039] The glass of the present invention contains zinc cations (especially Zn 2+) preferably in a proportion of 0 to 10 cationic %, for example 0.5 to 7.5 cationic %, or 1 to 5 cationic %. The proportion of zinc cations may be, for example, 2 to 10 cationic %, or 4 to 8 cationic %. The glass according to the invention may be free of zinc cations. In particular zinc cations may impair the chemical resistance. On the other hand zinc cations may be advantageous for meltability. The proportion of zinc cations may be, for example, at least 0.5 cationic %, at least 1 cationic %, at least 2 cationic %, or at least 4 cationic %. The proportion of zinc cations may be, for example, up to 10 cationic %, up to 8 cationic %, up to 7.5 cationic %, or up to 5 cationic %.
[0040] Preferably, the total percentage of magnesium cations, calcium cations, strontium cations, barium cations and zinc cations is in the range of 0-15 cation%, for example 1-10 cation%, 2-8 cation%, or 3-7 cation%. This percentage may be limited, especially to improve devitrification properties. The total percentage of magnesium cations, calcium cations, strontium cations, barium cations and zinc cations is preferably at most 15 cation%, more preferably at most 14 cation%, more preferably at most 13 cation%, more preferably at most 12 cation%, more preferably at most 11 cation%, more preferably at most 10 cation%, more preferably at most 9 cation%, more preferably at most 8 cation%, more preferably at most 7 cation%. The total percentage of magnesium cations, calcium cations, strontium cations, barium cations and zinc cations may be, for example, at least 1 cation%, at least 2 cation%, or at least 3 cation%.
[0041] The glass of the present invention is characterized in that it contains zirconium cations (especially Zr 4+) preferably in a proportion of 0 to 10 cationic %, for example 0.1 to 7.5 cationic %, or 0.5 to 5 cationic %. The proportion of zirconium cations may be, for example, 0 to 1 cationic %. Zirconium cations can increase the devitrification stability of the glass. In some embodiments, the proportion of zirconium cations is 1 to 9 cationic %, 1.5 to 8.5 cationic %, or 2 to 8 cationic %, for example at least 3 cationic %, at least 4 cationic %, or at least 5 cationic %. In other embodiments of the invention, the proportion of zirconium cations is less than 0.5 cationic %, or less than 0.1 cationic %. The glass of the invention may be free of zirconium cations. The proportion of zirconium cations may be, for example, at least 0.1 cationic %, at least 0.5 cationic %, at least 1 cationic %, at least 1.5 cationic %, at least 2 cationic %, at least 3 cationic %, at least 4 cationic %, or at least 5 cationic %. The percentage of zirconium cations may be, for example, up to 10 cation %, up to 9 cation %, up to 8.5 cation %, up to 8 cation %, up to 7.5 cation %, or up to 5 cation %.
[0042] The glass of the present invention is characterized by the presence of titanium cations (especially Ti 4+ ) preferably in a proportion of 0 to 10 cationic %, for example 0.5 to 8 cationic %, 0.75 to 6.5 cationic %, or 1 to 5 cationic %. The glass of the invention may be free of titanium cations. The proportion of titanium cations may be, for example, at least 0.5 cationic %, at least 0.75 cationic %, or at least 1 cationic %. The proportion of titanium cations may be, for example, up to 10 cationic %, up to 8 cationic %, up to 6.5 cationic %, or up to 5 cationic %.
[0043] Preferably, the glass according to the invention is free of antimony cations and / or arsenic cations.
[0044] In this disclosure, when it is stated that a glass is free of an ingredient or does not contain a particular ingredient, it means that this ingredient may be present in the glass at most as an impurity. This means that they are not added in an essential amount. An insubstantial amount is, according to the invention, an amount less than 0.02 cationic % (200 ppm), preferably less than 0.01 cationic % (100 ppm), preferably less than 0.005 cationic % (50 ppm), and in many cases preferably less than 0.001 cationic % (10 ppm).
[0045] Preferably, at least 90 cation %, more preferably at least 95 cation %, even more preferably at least 98 cation %, even more preferably at least 99 cation %, even more preferably at least 99.5 cation %, even more preferably at least 99.9 cation % of the cations of the glass are selected from the group consisting of cations of silicon, boron, aluminum, sodium, potassium, magnesium, calcium, zinc, zirconium, titanium, chromium and cobalt.
[0046] Due to the optical properties, the glass of the present invention is particularly suitable as a window glass for the housing of LIDAR.Because the glass of the present invention has a high transmittance in the NIR range and a low transmittance in the visible range.The glass can also be used, for example, in the fields of chemistry, space flight and traffic, especially for optical sensors.There are also other packaging applications.The glass can also be used in other technical fields, for technical applications or special pharmaceutical applications, and for glass tubes and glass articles with various geometric shapes (e.g. tubes, rods, disks, glass blocks).
[0047] For a sample thickness of 2 mm, the ratio of the minimum transmittance in the wavelength range 850 nm to 950 nm to the maximum transmittance in the wavelength range 250 nm to 700 nm is in the range of 1.9:1 to 15:1, for example 1.95:1 to 10:1, 2.00:1 to 7.5:1, 2.1:1 to 5:1, 2.2:1 to 4:1, or 2.5:1 to 3.5:1. The transmittance is preferably measured at intervals of 1 nm in the indicated range. From this, the minimum or maximum transmittance is preferably determined for each range and the corresponding ratio is calculated.
[0048] Preferably, the transmittance in the entire wavelength range of 850 nm to 950 nm is at least 75%, at least 76%, at least 77%, at least 78%, at least 79%, or at least 80%. Preferably, the minimum transmittance in the wavelength range of 850 nm to 950 nm is in the range of 75% to 99%, for example 76% to 95%, 77% to 92.5%, 78% to 91%, 79% to 90%, or 80% to 89%.
[0049] Preferably, the transmittance in the entire wavelength range of 880 nm to 930 nm is at least 75%, at least 76%, at least 77%, at least 78%, at least 79%, or at least 80%. Preferably, the minimum transmittance in the wavelength range of 880 nm to 930 nm is in the range of 75% to 99%, for example 76% to 95%, 77% to 92.5%, 78% to 91%, 79% to 90%, or 80% to 89%.
[0050] Preferably, the transmittance in the entire wavelength range of 250 nm to 700 nm is at most 50%, at most 45%, at most 40%, or at most 35%. Preferably, the maximum transmittance in the wavelength range of 250 nm to 700 nm is in the range of 1% to 50%, for example 10% to 45%, 20% to 40%, or 25% to 35%.
[0051] For a sample thickness of 2 mm, the ratio of the average transmittance in the wavelength range 850 nm to 950 nm to the average transmittance in the wavelength range 250 nm to 700 nm is in the range of 2:1 to 30:1, for example 2.5:1 to 25:1, 3:1 to 20:1, 4:1 to 15:1, or 5:1 to 12:1. The transmittance is preferably measured at intervals of 1 nm in the indicated ranges. From this, preferably for each range the average transmittance is calculated as the average of all transmittance values within said range.
[0052] Preferably, the average transmittance in the wavelength range of 850 nm to 950 nm is at least 75%, at least 76%, at least 77%, at least 78%, at least 79%, or at least 80%. Preferably, the average transmittance in the wavelength range of 850 nm to 950 nm is in the range of 75% to 99%, for example 76% to 95%, 77% to 92.5%, 78% to 91%, 79% to 90%, or 80% to 89%.
[0053] Preferably, the average transmittance in the wavelength range of 880 nm to 930 nm is at least 75%, at least 76%, at least 77%, at least 78%, at least 79%, or at least 80%. Preferably, the average transmittance in the wavelength range of 880 nm to 930 nm is in the range of 75% to 99%, for example 76% to 95%, 77% to 92.5%, 78% to 91%, 79% to 90%, or 80% to 89%.
[0054] Preferably, the average transmittance in the wavelength range of 250 nm to 700 nm is at most 25%, at most 22.5%, at most 20%, or at most 15%. Preferably, the average transmittance in the wavelength range of 250 nm to 700 nm is in the range of 0.1% to 25%, for example 1% to 22.5%, 2% to 20%, or 4% to 15%.
[0055] The transmittance properties of the glass can also be analyzed by determining the average transmittance in 20 nm wide subranges in the wider wavelength ranges 250 nm to 700 nm or 850 nm to 950 nm. For this, the transmittance is preferably first measured at 1 nm intervals in the indicated range. From this, for each 20 nm wide subrange in the wider wavelength ranges 250 nm to 700 nm or 850 nm to 950 nm, the average transmittance is calculated as the average value of all 21 transmittance values in the respective subrange. Thus, preferably 431 subranges in the range 250 to 700 nm and 81 subranges in the range 850 to 950 nm are analyzed.
[0056] Preferably, the ratio of the average transmittance of a 20 nm wide subrange having a minimum average transmittance in the range of 850 to 950 nm to the average transmittance of a 20 nm wide subrange having a maximum average transmittance in the range of 250 to 700 nm is in the range of 1.9:1 to 20:1, for example 2:1 to 15:1, 2.1:1 to 10:1, 2.2:1 to 7.5:1, 2.3:1 to 5:1, or 2.5:1 to 4.5:1.
[0057] Preferably, the average transmittance of the 20 nm wide subrange having the smallest average transmittance in the range of 850-950 nm is at least 75%, at least 76%, at least 77%, at least 78%, at least 79%, or at least 80%. Preferably, the average transmittance of the 20 nm wide subrange having the smallest average transmittance in the range of 850-950 nm is in the range of 75% to 99%, for example 76% to 95%, 77% to 92.5%, 78% to 91%, 79% to 90%, or 80% to 89%.
[0058] Preferably, the average transmittance of a 20 nm wide subrange having a maximum average transmittance in the range of 250-700 nm is at most 50%, at most 45%, at most 40%, or at most 35%. Preferably, the average transmittance of a 20 nm wide subrange having a maximum average transmittance in the range of 250-700 nm is in the range of 1% to 50%, for example 10% to 45%, 15% to 40%, or 20% to 35%.
[0059] Unless otherwise stated, statements made in this disclosure regarding transmittance include reflection losses as well, not just pure transmittance values.
[0060] The glass of the present invention not only has excellent optical properties. The glass of the present invention is also characterized by a particularly high crystallization resistance. This is particularly important for production in tube drawing. Otherwise, devitrification crystals may occur, especially on the glass surface, which would, for example, prevent the shaping of the glass. Thus, the glass has good devitrification stability. This is particularly important for large dimensions and thick walls.
[0061] One measure of crystallization resistance is the maximum crystallization rate KG max It is. max The smaller the KG, the greater the resistance to crystallization. In this disclosure, the terms "crystallization resistance" and "devitrification stability" are used synonymously. max describes the maximum crystallization rate (usually in μm / min). Measurement of crystallization rate is known. Preferably, the crystallization rate is measured along the crystals that are formed, i.e. along their maximum extent.
[0062] According to the invention, "UEG" is understood as the so-called lower devitrification limit. This is the temperature at which the devitrification of the material begins under elevated temperature operation. Above a certain temperature, called the upper devitrification limit (OEG) or liquidus temperature, no crystallization occurs even after a long time. The numerical values of UEG and OEG usually differ for different glasses.
[0063] If crystallization does occur, it will occur at a temperature above the lower devitrification limit (UEG) and below the upper devitrification limit (OEG), i.e., in the range between UEG and OEG. Therefore, the temperature at which the maximum crystallization rate is reached is also between UEG and OEG. Therefore, the maximum crystallization rate KG max To measure KG, the glass must be heated to a temperature between UEG and OEG. Since it is not known exactly where in the range between UEG and OEG the maximum crystallization will occur for a particular glass, the KG maxIn this manner, the UEG and OEG themselves can be determined as the lower or upper limits of the range over which crystallization occurs.
[0064] In particular, the crystallization rate is measured by heat-treating the glass in a gradient furnace for a holding time of 1 hour with a ramp. A gradient furnace is a furnace with different heating zones, i.e. with different temperature regions. A ramp means that the temperature of the glass before being introduced into the gradient furnace is lower than the temperature in all regions of the furnace. The introduction into the furnace therefore increases the temperature of the glass, regardless of the region of the furnace into which the glass is introduced. The measurement of devitrification is therefore carried out in particular by heat-treating for 1 hour in a (already hot) gradient furnace, which is divided into different temperature regions. This is a spatially resolved temperature gradient in the gradient furnace, but not a time resolved gradient, since the gradient furnace is spatially resolved and divided into zones of different temperatures.
[0065] Due to the fact that the gradient furnace is divided into several heating zones, different temperatures can be tested simultaneously. This is a special advantage of the gradient furnace. For example, the minimum temperature can be 950°C and the maximum temperature 1250°C, or the minimum temperature can be 700°C and the maximum temperature 1000°C. The temperatures should be selected so that the crystallization rate can be measured at different temperatures in the range between UEG and OEG, so that from the comparison of different crystallization rates that may be in the range between UEG and OEG, the highest crystallization rate can be determined as the maximum crystallization rate KG. max When the UEG and OEG are unknown, it is advantageous to test over a relatively wide range of temperatures to allow for the measurement of the UEG and OEG.
[0066] Therefore, when the glass is heat treated in a gradient furnace with a temperature ramp for a holding time of 1 hour, the glass has a maximum crystallization rate (KG) of up to 0.20 μm / min in the temperature range of 700°C to 1250°C. max) does not mean that there must be temperatures in the entire range of 700°C to 1250°C in the gradient furnace. For example, if the OEG for a particular glass is known to be 1000°C, there is no need to test temperatures above 1000°C in the gradient furnace, since crystallization does not occur at this temperature in the first place and the maximum crystallization rate KG max Similarly, if, for example, the UEG for a glass is known to be 950°C, there is no need to test temperatures below 950°C in a gradient furnace, since crystallization does not occur at this temperature in the first place and the maximum crystallization rate KG max must exist above 950°C.
[0067] If devitrification does not occur, no crystallization will occur, so KG max cannot be measured. In this case, KG max A value of 0 μm / min can be assumed for
[0068] The crystallization rate is preferably measured using glass grains, in particular glass grains having a diameter of 1.6 mm to 4 mm. The glass grains are preferably placed on a support, for example a platinum support, for the heat treatment in a gradient furnace. The support may in particular have recesses for accommodating each glass grain and holes below each recess, so that following the heat treatment the crystallization rate can be measured microscopically. In view of the preferred size of the glass grains, the recesses preferably each have a diameter of 4 mm and the holes each have a diameter of 1 mm. Following the heat treatment, it can be determined microscopically which crystallization rate was present in which temperature range. The highest crystallization rate that is identified is referred to as the maximum crystallization rate KG max The UEG and OEG can be determined as the lower and upper limits of the temperature range where crystallization occurs. The allocation of individual glass grains to different temperature zones in the gradient furnace is not an issue because it is known which temperature exists at which location in the furnace and where the glass grain was located in the furnace.
[0069] The glass of the present invention has a maximum crystallization rate (KG) in the temperature range of 700°C to 1250°C, especially when the glass is heat treated in a gradient furnace with a temperature ramp for a holding time of 1 hour. max ) is preferably up to 0.20 μm / min. More preferably, KG max It is particularly preferred that no devitrification occurs when the glass is heat-treated in a gradient furnace by a temperature ramp for a holding time of 1 hour, and thus the KG max is particularly preferably 0 μm / min.
[0070] Preferably, in particular if the glass is heat treated in a gradient furnace with a temperature ramp for a holding time of 1 hour, KG max is at most 0.20 μm / min, more preferably at most 0.15 μm / min, even more preferably at most 0.10 μm / min, even more preferably at most 0.05 μm / min, even more preferably at most 0.04 μm / min, even more preferably at most 0.03 μm / min, even more preferably at most 0.02 μm / min, and even more preferably at most 0.01 μm / min in a temperature range of 700° C. to 1250° C., for example, 700° C. to 1205° C., 700° C. to 1190° C., 700° C. to 1115° C., 885° C. to 1190° C., 835° C. to 1140° C., and / or 1060° C. to 1155° C. Particularly preferably, in the temperature range from 700° C. to 1190° C., for example from 700° C. to 1115° C., from 885° C. to 1190° C., from 835° C. to 1140° C., and / or from 1060° C. to 1155° C., devitrification does not occur, especially when the glass is heat-treated in a gradient furnace with a holding time of 1 hour, and thus KG max is particularly preferably 0 μm / min.
[0071] Due to its excellent devitrification stability, the glasses of the invention can be produced in any known glass forming process, in particular in tube drawing processes, such as in the Danner process, in the Vello process or in the A-draw process (vertical draw process).
[0072] Furthermore, the glasses according to the invention have a particularly high hydrolysis resistance, in particular a hydrolysis resistance according to hydrolysis class 1 according to USP660, ISO719 and / or ISO720. Preferably, the glasses have a hydrolysis resistance HGB1 according to ISO719. Preferably, the glasses have a hydrolysis resistance HGA1 according to ISO720:1985. Preferably, the glasses have a hydrolysis resistance of type I according to USP660 / glass grain. Particularly preferably, the glasses have a hydrolysis resistance corresponding to at most 90%, more preferably at most 89%, more preferably at most 88%, more preferably at most 87%, more preferably at most 85%, more preferably at most 80%, more preferably at most 75%, more preferably at most 70% of the limit value of type I according to USP660 / glass grain. The limit value of type I corresponds to 0.10 ml 0.02 N HCl.
[0073] A particular advantage of the glasses of the invention is that they combine favourable transmission properties with good crystallisation resistance and good hydrolysis resistance.
[0074] The glass of the present invention can preferably be chemically strengthened, which can increase the stability against environmental influences, especially hail, for example. Chemical strengthening includes, in particular, an ion exchange treatment, in particular the exchange of smaller ions for larger ions. Usually, sodium ions are exchanged for potassium ions, in particular a treatment in a potassium salt, for example a KNO3 bath, is carried out.
[0075] A measure of the strengthening is the diffusion coefficient D (also called the threshold value for the diffusion coefficient D) (English "diffusivity D" or "threshold diffusion coefficient D"). The diffusion coefficient D can be calculated from the penetration layer depth (English "depth of layer (DoL)") and the chemical strengthening time t according to the following formula: DoL = 1.4 × (4 × D × t) 1 / 2
[0076] In this disclosure, D is shown for chemical strengthening in KNO3 at 450°C for 9 hours. The statement of the diffusion coefficient does not represent that the glass has actually been chemically strengthened. Rather, the diffusion coefficient is a measure of the temperability of the glass.
[0077] Preferably, the diffusion coefficient D is between 5 and 50 μm per hour. 2 , and more preferably 7.5 to 40 μm per hour 2 , and more preferably 10 to 30 μm per hour 2 , and more preferably 15 to 25 μm per hour 2 The diffusion coefficient D is, for example, at least 5 μm per hour. 2 , at least 7.5 μm per hour 2 , at least 10 μm per hour 2 , or at least 15 μm per hour 2 The diffusion coefficient D may be, for example, up to 50 μm per hour. 2 , up to 40μm per hour 2 , up to 30μm per hour 2 , or up to 25 μm per hour 2 It may be.
[0078] The glass of the invention preferably has a relatively low density, in particular between 2.20 and 2.80 g / cm 3 , and more preferably 2.25 to 2.75 g / cm 3 , more preferably 2.30 to 2.70 g / cm 3 The density is, for example, at least 2.20 g / cm 3 , at least 2.25 g / cm3 , or at least 2.30 g / cm 3 The density may be, for example, up to 2.80 g / cm 3 , max 2.75g / cm 3 , or up to 2.70 g / cm 3 It may be.
[0079] The coefficient of thermal expansion (CTE) in the temperature range 20° C. to 300° C. is preferably in the range of 4 to 9 ppm / K, more preferably 4.5 to 8.5 ppm / K, even more preferably 5 to 8 ppm / K. The CTE may for example be at least 4 ppm / K, at least 4.5 ppm / K, or at least 5 ppm / K. The CTE may for example be at most 9 ppm / K, at most 8.5 ppm / K, or at most 8 ppm / K.
[0080] Glass transition temperature T g The glass transition temperature T is preferably in the range of 450°C to 700°C, more preferably 475°C to 685°C, and even more preferably 500°C to 675°C. g For example, the glass transition temperature T may be at least 450° C., at least 475° C., or at least 500° C. g may be, for example, up to 700°C, up to 685°C, or up to 675°C.
[0081] The working temperature VA is preferably in the range of 1000° C. to 1250° C., more preferably 1025° C. to 1225° C. The working temperature VA may for example be at least 1000° C., or at least 1025° C. The working temperature VA may for example be up to 1250° C., or up to 1225° C.
[0082] Viscosity is 10 2The temperature T2 in dPas is preferably in the range of 1250° C. to 1750° C., for example 1300° C. to 1500° C. or 1350° C. to 1450° C. The temperature T2 may for example be at least 1250° C., at least 1300° C. or at least 1350° C. The temperature T2 may for example be up to 1750° C., up to 1500° C. or up to 1450° C.
[0083] The present invention also relates to a glass article comprising a glass according to the invention. Preferably, said glass article has a thickness of at most 5 mm, such as at most 4 mm, at most 3 mm, or at most 2 mm. Preferably, the thickness of said glass article is in the range of 0.02 mm to 5 mm, such as 0.03 mm to 4 mm, 0.05 mm to 3 mm, or 0.07 mm to 2 mm. Said thickness may for example be at least 0.02 mm, at least 0.03 mm, at least 0.05 mm, or at least 0.07 mm. The glass article may be present in various geometric shapes, such as tubes, rods, discs, films or glass blocks. In the case of a glass tube, the thickness of the glass article refers to the wall thickness of the tube.
[0084] The glass article may contain, in addition to the glass according to the invention, further layers, in particular one or more anti-reflective layers, heatable layers, anti-fouling layers (in particular hydrophobic or oleophobic) and / or (in particular on the outside) scratch-resistant layers.
[0085] The present invention also relates to a method for producing a glass or glass article according to the invention, said method comprising the following steps: melting the glass raw materials; processing the glass melt, in particular by downdraw, overflow fusion, redraw, float or tube drawing, in particular by the Danner, Vello or A-draw processes (vertical draw processes), cooling the resulting glass or glass article. Includes.
[0086] Due to its excellent devitrification stability, the glass of the present invention can be produced by tube drawing, in particular by the Danner process, the Vello process, or the A-draw process (vertical draw process).The A-draw process is particularly preferred, since it allows particularly large tube diameters to be achieved, for example outer diameters of more than 30 mm, or even more than 50 mm.In some embodiments, the outer diameter is up to 500 mm.
[0087] Preferably, the method comprises a step of chemical hardening, in particular by ion exchange, of the glass or glass article. Preferably, the chemical hardening comprises ion exchange, in particular in a KNO3 bath, at a temperature of 320°C to 700°C, particularly preferably 400°C to 500°C. The duration of the chemical hardening, in particular the duration of the ion exchange treatment, is preferably in the range of 5 minutes to 48 hours, more preferably 1 hour to 24 hours, more preferably 4 hours to 15 hours, more preferably 5 hours to 12 hours. Particularly preferred is chemical hardening at 450°C for 9 hours.
[0088] The present invention also relates to the use of the glass or glass article according to the present invention, for example in the fields of chemistry, space flight and traffic, especially for optical sensors.The use in dual sensor systems is also according to the present invention.The present invention also relates to the use of the glass or glass article as packaging.The present invention also relates to technical or pharmaceutical uses of the glass or glass article.The use of the glass or glass article in the field of LIDAR, especially as a window pane for the housing of LIDAR, or as a housing of LIDAR or a cover of LIDAR, is particularly preferred. [Brief description of the drawings]
[0089] [Figure 1] Figure 1 shows the transmission spectra of the samples of Example Glasses 1 to 4 in the wavelength range 250 nm to 2500 nm. The spectra were measured on samples with a wall thickness of about 2 mm (1.96 to 2.01 mm). Since the spectra can only be compared for samples with exactly the same thickness, thicknesses that deviate from 2 mm were converted to 2 mm respectively. EXAMPLES
[0090] The invention is illustrated below by means of examples.
[0091] Glass composition The following table gives the glass compositions in cation % for example glasses 1-4 according to the invention, as well as two comparative examples, Comparative 1 and Comparative 2. Thus, the relative molar percentage of each of the listed component cations relative to the total cations of the glass is given.
[0092] [Table 1]
[0093] The glasses 1 to 4 of the examples are tube drawable. In contrast, the glasses 1 and 2 of the comparative examples have too high a tendency to devitrification. max is 0.8 μm / min for both Comparative Examples 1 and 2, respectively, when the glasses are heat treated by a temperature ramp in a gradient furnace for a holding time of 1 hour.
[0094] optical properties The optical properties of the example glasses of the present invention were measured on samples with a wall thickness of about 2 mm (1.96 to 2.01 mm). Since the spectra can only be compared for samples with exactly the same thickness, thicknesses that deviate from 2 mm were converted to 2 mm respectively.
[0095] The glasses of the present invention have low transmittance in the visible range and high transmittance in the NIR range. For each of Examples 1-4, two samples were investigated. Exemplary transmittance curves are shown in FIG. 1 for each of the two samples in Examples 1-4. A detailed analysis of the transmittance characteristics is presented below. The transmittance values shown are not pure transmittance values but also include reflection losses.
[0096] Maximum and minimum transmission The table below shows the minimum transmittance in the wavelength range 850-950 nm, the maximum transmittance in the wavelength range 250-700 nm, and the ratio of the two values. The transmittance was measured at intervals of 1 nm in the ranges shown. From this, the minimum or maximum transmittance for each range was determined and the corresponding ratio was calculated.
[0097] The following table shows rounded values. The ratios shown were calculated based on unrounded transmittance values, so there may be differences compared to the ratios calculated from the rounded transmittance values shown. For each example glass (Example 1 to Example 4), the results of the two samples investigated (Sample 1 and Sample 2) are shown.
[0098] [Table 2]
[0099] For all examples and samples, the minimum transmittance in the wavelength range of 850 nm to 950 nm was clearly higher than the maximum transmittance in the wavelength range of 250 nm to 750 nm, and therefore the examples have the transmittance characteristics according to the invention.
[0100] average transmittance The table below gives the average transmittance in the wavelength range 850-950 nm, the average transmittance in the wavelength range 250-700 nm, and the ratio of the two values. The transmittance was measured at intervals of 1 nm in the ranges shown. From this, for each range, the average transmittance was calculated as the average of all the transmittance values within said range.
[0101] [Table 3]
[0102] For all examples and samples, the average transmittance in the wavelength range of 850 nm to 950 nm was clearly higher than the average transmittance in the wavelength range of 250 nm to 750 nm, and therefore the examples have the transmittance characteristics according to the invention.
[0103] Average transmittance in a subrange The transmittance properties of the glasses were further analyzed by determining the average transmittance in 20 nm wide subranges within the broader wavelength ranges of 250 nm to 700 nm or 850 nm to 950 nm.
[0104] The transmittance was measured at 1 nm intervals in the ranges shown. From this, for each 20 nm wide subrange within the broader wavelength ranges of 250-700 nm or 850-950 nm, the average transmittance was calculated as the average of all 21 transmittance values within each subrange. For each sample, 431 subranges in the 250-700 nm range and 81 subranges in the 850-950 nm range were analyzed.
[0105] The following table shows the average transmittance of the subrange having the smallest average transmittance in the range 850-950 nm, and the subrange having the largest average transmittance in the range 250-700 nm. The ratio of these two values is also shown.
[0106] [Table 4]
[0107] Even in the case of the partial range analysis, it was found that for all examples and samples the minimum transmittance in the wavelength range 850 nm to 950 nm is clearly higher than the maximum transmittance in the wavelength range 250 nm to 750 nm, and therefore the examples have the transmittance characteristics according to the invention.
Claims
1. Maximum crystallization speed (KG) of up to 0.20 μm / min in the temperature range of 700° C. to 1250° C. max ) and a hydrolysis resistance according to hydrolysis class 1 (HGA1 according to ISO 720:1985), wherein the ratio of the minimum transmittance in the wavelength range 850 nm to 950 nm to the maximum transmittance in the wavelength range 250 nm to 700 nm is in the range of 1.9:1 to 15:1 for a sample thickness of 2 mm, Cations of the following components: Ingredients Proportion Silicon 50-70 Boron 0-20 Aluminum 0-25 Sodium 2-22 Potassium 0.5-9 Chromium 0.05 to 0.5 Cobalt 0.03 to 0.5 in the indicated percentages (cation %), wherein the combined percentage of sodium and potassium cations is in the range of 11 to 22.5 cation %, the combined percentage of chromium and cobalt cations is in the range of 0.15 to 0.55 cation %, and the combined percentage of magnesium, calcium, strontium, barium, and zinc cations is up to 15 cation %, and the ratio of the molar percentage of sodium cations (cation %) to the molar percentage of potassium cations (cation %) is 0.5:1 to 25:
1.
2. Cations of the following components: Ingredients Proportion Magnesium 0-5 Calcium 0-15 Strontium 0-5 Barium 0-5 Zinc 0-10 Zirconium 0 to 10 Titanium 0-10 2. The glass of claim 1 comprising the indicated percentages (cation %) of:
3. The glass is 5 to 50 μm per hour. 2 3. The glass of claim 1, having a diffusion coefficient D in the range
4. 4. The glass of claim 1, having a transmission of at least 75% over the entire wavelength range from 850 nm to 950 nm.
5. 5. The glass of claim 1, wherein the ratio of the sum of the molar proportions of sodium and potassium cations to the sum of the molar proportions of cobalt and chromium cations is in the range of 25:1 to 150:
1.
6. 6. A glass article comprising the glass of any one of claims 1 to 5, said glass article having a thickness in the range of 0.02 mm to 5 mm.
7. A method for producing a glass according to any one of claims 1 to 5 or a glass article according to claim 6, comprising the steps of: - melting glass raw materials; processing the glass melt, in particular by downdraw, overflow fusion, redraw, float or tube drawing, in particular by the Danner, Vello or A-draw processes (vertical draw processes), cooling the resulting glass or glass article; The method comprising:
8. The following steps: Chemically hardening the glass or glass article by ion exchange. The method of claim 7, comprising:
9. 7. Use of the glass according to any one of claims 1 to 5 or the glass article according to claim 6 as a LIDAR housing or a LIDAR cover.
Citation Information
Patent Citations
Glass for near infrared transmitting black filter
JP1995126036A
colored soda lime glass
JP2005529044A
Ion-exchangeable colored glass containing a transition metal
JP2016504986A
Glass sheet with high infrared transmission
JP2017501101A
Protective housing for a sensing device
WO2019030106A1